2020
DOI: 10.3856/vol48-issue4-fulltext-2464
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of probiotics in freshwater prawn (Macrobrachium sp.) culture in biofloc systems

Abstract: This document is an updated review on the use of probiotics to the freshwater prawn Macrobrachium sp. culture in biofloc systems, pointing out the benefits in growth, survival, improvements in the immune system, pathogen control, and water quality. The review also emphasizes some aspects that need to be defined with greater accuracy, like the effect of doses and times of probiotic administration and refers to bacterial dynamics associated with biofloc. This review aims to enhance the knowledge of probiotics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The differences may be due to some experimental procedures from their duration, age stage of shrimp, water use, type of feed and environmental conditions. A review study was conducted on the uses of probiotics in shrimp farms, especially carpentry species Macrobrachium sp., to increase knowledge (Cienfuegos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The differences may be due to some experimental procedures from their duration, age stage of shrimp, water use, type of feed and environmental conditions. A review study was conducted on the uses of probiotics in shrimp farms, especially carpentry species Macrobrachium sp., to increase knowledge (Cienfuegos et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The application of probiotic species such as Lactobacillus sporogenes, Bacillus subtilis and Saccharomyces cerevisiae give significant effect to the post larvae growth and enzymatic production of protease, amylase and lipase in the M. rosenbergii post-larvae culture (Martinez et al, 2020). The FCR was lower in the prawn cultured in biofloc tank as compared to the prawn cultured in RAS (Nguyen et al, 2019).…”
Section: Biofloc Applications In Freshwater Prawn Aquaculturementioning
confidence: 99%
“…A research conducted on Chilean river shrimp, Cryhiops caementarius identified that higher survival was obtained from biofloc system about 93% with 5.96% higher growth level as compared to clear water around 87% survival rate (Walker et al, 2020). The use of probiotics to the freshwater prawn cultured in biofloc system found out its help give beneficial effects to the prawn growth, survival, help improves the immune system and disease resistance as well as help sustains a good water quality (Martinez et al, 2020).…”
Section: Biofloc Applications In Freshwater Prawn Aquaculturementioning
confidence: 99%